Contribution of concrete cultural constituents to the tourism potential of Safranbolu - KURT, HALİL (ELSEVIER SCIENCE BV, 2011)
Safranbolu is one of the richest towns in Turkey in terms of culture and history. It has a wide range of historical and cultural background. Safranbolu had been under the influence of Hellenistic period, Byzantium and Ottoman civilizations according to the explorations in the region. Among the properties of Safranbolu there are Safranbolu Houses, mosques, tombs, dervish lodges, inns, baths, bridges, fountains and libraries that can be considered valuable in terms of tourism potential. Safranbolu houses reflect the history, culture, economy and ways of living in the 18th and 19th centuries. Houses built in and around the valleys also reflect the geographical and environmental features of Safranbolu. Those houses and building have their own designs. Tas Minare Mosque, Koprulu Mehmet Pasa Mosque, Hidayetullah Mosque and Dagdelen Mosques are some of the historical ones that reflect the culture of their time. There are tombs which were built in the 19th century. Haci Emin Efendi Tomb, Hasan Baba Tomb, Seyh Mustafa Efendi Tomb are among them. It is possible to mention about two major dervish lodges one of which is Kalealti Lodge and the other is Ali Baba Lodge. Among the baths there are two significant ones; one of them is the old bath and the other is the new bath reflecting 14th century. Bridges and fountains are other cultural constituents in which have contributions to the tourism potential. (C) 2011 Published by Elsevier Ltd. Selection and/or peer-review under responsibility of The 2nd International Geography Symposium-Mediterranean Environment
Keywords: tourism potential; culture; cultural constituents; civilization